1980
DOI: 10.1002/pssb.2221000128
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Planar Channeling of Relativistic Protons in Bent Crystals

Abstract: Dechanneling of relativistic protons in planar channels of bent crystals is examined on the basis of the Fokker-Planck equation. The dependence of the dechanneling half-length x 1 p in a curved channel of (110) Si on the particle energy E and the bending radius R is found. It is shown that in the bent crystal the dechanneling lengths are considerably reduced and the proportionality between the x1/2 value and the particle energy E is violated. The optimum conditions for deflection of a proton beam a t the defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Thus, one should expect the presence of optimal radius of curvature in the case of planar channeling of negatively charged particles in a bent crystal. It should be noted that the existence of the optimal radius of crystal curvature for positively charged particles deflection had been shown for the first time in [9] and the analytical expression for the optimal crystal curvature for positively charged particles was suggested in [10,11].…”
Section: Optimal Radius Of Curvaturementioning
confidence: 99%
“…Thus, one should expect the presence of optimal radius of curvature in the case of planar channeling of negatively charged particles in a bent crystal. It should be noted that the existence of the optimal radius of crystal curvature for positively charged particles deflection had been shown for the first time in [9] and the analytical expression for the optimal crystal curvature for positively charged particles was suggested in [10,11].…”
Section: Optimal Radius Of Curvaturementioning
confidence: 99%
“…Theoretical analysis of various phenomena related to the channeling in bent crystals (classical treatment), including the dechanneling effect, can be found in [94,95,97,189,274]. The review of theoretical models and computational methods can be found in [68,271].…”
Section: Channeling In Bent Crystalsmentioning
confidence: 99%
“…This change, ∆n 0 , is the smallest for the straight channels and its magnitude increases with C. Such a behaviour is explained as follows. The probability for the projectile to undergo the largeangle scattering from the crystal electrons or/and nuclei is proportional to the volume densities n el (ρ) and n n (ρ) (see (46)(47)(48)(49)(50)). The large-angle scattering, i.e.…”
Section: Numerical Results Of the Dechanneling Process Simulationsmentioning
confidence: 99%
“…The first approach is based on the diffusion theory applied to describe the multiple scattering (e.g. [11,17,48,49]. The second approach is in direct computer simulation of the scattering process [50,12].…”
Section: Equations Of Motion With Account For the Random Collisions W...mentioning
confidence: 99%